Analysis of Liquefaction Potential Based on Seismic Wave Velocity in Bengkulu City - Arif Setiawan; Della Zakia Sholeha; Alfata Kausari; Arif Ismul Hadi (Lambung Mangkurat University Press, 2023)
Bengkulu City has a high liquefaction rate, both geologically and geophysically. This is because Bengkulu City consists of rocks in the form of sand, silt, mud, clay, coral fragments and gravel in alluvial areas (Qa) and floodplains. Terrace formation (Qat). This study aims to analyze liquefaction potential using seismic waves in Bengkulu City, resulting in a layer profile (Vs) obtained from the Vs30 soil of Bengkulu City and a classification of areas with liquefaction potential. This study was conducted using a PASI 16S-24P seismograph, a set of seismic equipment used in the study area, which obtained Vs profiles derived from 24 geophones 4 m and 8 m away from each study location. Then, the RMS error and standard deviation values were generated. The result of MASW analysis data describes the Vs and Vs30 profiles in the Bengkulu City subsoil that can be classified into soil zones. Soil results at the study site show different site classes, namely B, C, D and E. Liquefaction potential can be analyzed with Vs profiles. It shows the existence of different layers in the Bengkulu city area. It can be seen that Bengkulu City is dominated by sand and gravel, causing very high liquefaction, especially in the Surabaya area, where the Vs and Vs30 soil values have soft soil values with sensitivity values of 134.0 to 171.0 m/s. Soil classification is highly sensitive to liquefaction. The study areas of Lempuing and Rawa Makmur sub-districts generally show medium liquefaction potential, and the Teluk Sepang sub-district area shows low liquefaction potential.